Perspektif Gender dalam Novel Bekisar Merah Karya Ahmad Tohari: Kajian Sastra Feminis dan Implementasinya dalam Pembelajaran Sastra di SMA - Rita Nilawijaya; Awalludin Awalludin (LP4MK STKIP PGRI Lubuklinggau, 2021)
Novels are unique in telling every event in the life of the main character. Likewise, in the novel Bekisar Merah by Ahmad Tohari, he tries to tell the main female character from a gender perspective according to his era. For this reason, this study aims to describe: 1) the structure of the novel Bekisar Merah by Ahmad Tohari, 2) the manifestation of gender equality in the novel Bekisar Merah by Ahmad Tohari, and 3) the implementation of research results in the novel Bekisar Merah by Ahmad Tohari in learning literature in high school. The data in this study are in the form of words, sentences, expressions, and discourses that contain elements of gender issues in the novel Bekisar Merah. The sampling technique used is purposive sampling, while the data collection uses documentation and note-taking techniques. Test the validity of the data applied, namely member check and validation of literary experts. The data analysis technique used a semiotic model reading technique consisting of heuristic and hermeneutic readings. The results of the study show that: 1) the structure of the novel Bekisar Merah, which is based on Stanton's fictional theory, carries the theme of women's struggles in realizing gender equality with men. The facts of the novel are divided into three, namely: characters and characterizations, setting, and storyline. 2) The forms of gender equality contained in the novel are: (a) women as equal partners of men, (b) equal rights and obligations between men and women, and (c) opponents of violence against women. 3) The results of the study were implemented in a learning scenario with KD 7.2 analyzing the intrinsic and extrinsic elements of the novel. Thus, it can be concluded that the novel Bekisar Merah by Ahmad Tohari can be implemented in learning literature in high school.